Alinhamento, estratégia empresarial e competências de gestão de pessoas : análise de suas inter-relações em empresas no norte do Paraná - Zagui, Cristiane (2010)
In a time where the great majority of the contemporary organizations seek for new models of managing people, the ones that can give to the enterprises the capability of becoming a more strategic marketing actor, this research aims to offer some contributions able of increasing these discussions by examining some of the inter-relations possible of being observed in links between the organizational strategies and the respective corporate competences of managing its workers. In a more specific speech, for this dissertation it is trodden a path for which it is also, and mainly, desired: to identify the core strategies of the organizations studied, to identify competences of managing people in these organizations and to elaborate a hypothetic causal trail capable of aligning that strategies with these competences. From this moment on it is discusses if these themes are or are not aligned in the enterprises analyzed in field. Because of the characteristics that surround the corporate cases investigated it has been necessary to follow some methodological steps that qualify this research as mixed (both quantitative and qualitative). For the data collection it has been used two empirical research instruments: a structured questionnaire and a focal group. The treatment of the data collected has been done with the help of analysis guided by the descriptive statistic and enriched by content analysis, a technique applied to study the declarations offered by the focal group. The results show that, in general, the competences of managing workers are not aligned with the core strategies in the corporations studied. Between the causes that motivates this situation, it is highlighted the non dissemination of the strategic planning, the difficulty of communication by the managers that cannot specify the mainly strategic objectives of the enterprise where they work and the lack of prepare of the human resource department in dealing with the alignment investigated in this dissertation. It is possible to conclude that besides of the activities related to the competences of managing people being assumed as realized apart of the alignment proposed by this research, the organizations investigated tend to suffer some inconveniences as: less efficiency in managerial process, higher costs due to the continuum turn-over, less engagement of the employees, difficulty in retaining talented people and a constant increase in the cost of the activities related to the human resources department. By all this, it is stated that: the department that has the potential of fostering the organizational results does not realize its functions with efficiency and, for this, does not become a strategic department.